Phisycal And Chemical Properties And Nutrient Content (N, P, K, Mg, B, Cu And Zn ) In Oil Palm Leaf In Various Of Age After Compacting - Eko Kurniawan; Nelvia Nelvia; Wawan Wawan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2020)
Planting of oil palm in peatland has been limited by soil physical, chemical properties, and hydrology, that`s way needed improvement on those matters to increase the productivity of peat and oil palm in peat soil by compacting. The purpose of this compacting is to improve the soil's physical, chemical properties, and soil moisture. A sampling of soil, water, and leaf were done in consecutive block 5,4,3,2,1,0 year after compacting and of planting done 4 years 10 months, 3 years 9 months, 2 years 9 months, 1 year 10 months, 11 months and 2 months, control used in this trial are origin condition (forest). Increasing bulk density was found at compacting block with 30 cm depth from the surface with the lower in 2 years after compacting at 0.09 g/cm3 and highest 4 years after compacting 0.4 g/cm3. In-depth of 60 cm from surface was found no increasing the bulk density 3 years after compacting 0.0 g/cm3 and the highest on 5 years after compacting 0.3 g/cm3 compared to forest. Decreasing on permeability in-depth 30 cm at 4 years after compacting 7.47 cm/jam and close to forest permeability 51.11 cm/hour is 2 years 43.6 cm/hour. As represent rise capillary consistently water content ≥ 80% achieved at depth 20 cm of surfaces on all block. Compaction doesn't regard pH, C organic, basa's saturation, capacity exchange cation. On depth 30 cm P-total lower on s without compaction at 599.6 ppm and above 871.6 ppm on 5 yr than forest 585 ppm. P available most low 58.1 ppm happens on 4 yr afters is compacted and p available forest 53.9 ppm. Nutrient content B, Cu and Zn at soil not influenced by compaction. Fosfor (P) in water increases with added years after compaction lower at 39.1 mg/L in the block without compaction compare of forest that 40.8 mg/L. Leaf nutrient rate on compacted block on optimum until excess where N (2. 69 – 3.15 %) , P (0. 170 – 0.209 %) , K( 0. 952 – 1.11%) , Mg ( 0. 377 – 0.497%) , except on block without compacting K (0. 830 %) and Mg (0. 190%) at deficiency and 0 years afters compaction Mg leaf on level deficiency 0. 230%. Nutrient content of B, Cu and Zn at various level and not influenced by compacting.